A multimethod research investigation of consumer involvement in Australian health service accreditation programmes: the ACCREDIT-SCI study protocol. Issue 5 (10th October 2012) - Greenfield, David; Hinchcliff, Reece; Moldovan, Max; Mumford, Virginia; Pawsey, Marjorie; Irene Westbrook, Johanna; Braithwaite, Jeffrey
Abstract : Introduction: Health service accreditation programmes are a regulatory mechanism adopted to drive improvements inpatient safety and quality. Research investigating the benefits or limitations, of consumer involvement in accreditation programmes is negligible. To develop our knowledge in this area the ACCREDIT collaboration (Accreditation Collaborative for the Conduct of Research, Evaluation and Designated Investigations through Teamwork) has developed a research plan, known as the ACCREDIT-SCI (Standards of Consumer Involvement) study protocol. Two complementary studies have been designed: one, to examine the effectiveness of a standard for consumer participation and two, to explore how patient experiences vary across a range of settings with differing accreditation results. Methods and design: The research setting is the Australian healthcare system, and the two studies focus on three accreditation programmes in the primary, acute and aged care domains. The studies will use multimethods: document analysis; interviews and surveys. Participants will be stakeholders across the three domains including: policy officers; frontline healthcare professionals; accreditation agency personnel, including surveyors and healthcare consumers. Drawing on previous experience, the research team has developed purpose-designed tools. Data will be analysed using thematic, narrative and statistical (descriptive and inferential) procedures. Ethics and dissemination: The University of New South Wales Human Research Ethics Committee has approved the two studies (HREC 10274). Findings will be disseminated through seminars, conference presentations, academic publications and research partner websites. The findings will be formulated to facilitate uptake by policy and accreditation agency professionals, researchers and academics, and consumers, nationally and internationally.